Growth of modern branched columnar stromatolites in Lake Joyce, Antarctica. Issue 4 (13th April 2015) - Mackey, T. J.; Sumner, D. Y.; Hawes, I.; Jungblut, A. D.; Andersen, D. T.
Abstract Modern decimeter‐scale columnar stromatolites from Lake Joyce, Antarctica, show a change in branching pattern during a period of lake level rise. Branching patterns correspond to a change in cyanobacterial community composition as preserved in authigenic calcite crystals. The transition in stromatolite morphology is preserved by mineralized layers that contain microfossils and cylindrical molds of cyanobacterial filaments. The molds are composed of two populations with different diameters. Large diameter molds (>2.8 μm) are abundant in calcite forming the oldest stromatolite layers, but are absent from younger layers. In contrast, <2.3 μm diameter molds are common in all stromatolites layers. Loss of large diameter molds corresponds to the transition from smooth‐sided stromatolitic columns to branched and irregular columns. Mold diameters are similar to trichome diameters of the four most abundant living cyanobacteria morphotypes in Lake Joyce: Phormidium autumnale morphotypes have trichome diameters >3.5 μm, whereas Leptolyngbya antarctica, L. fragilis, and Pseudanabaena frigida morphotypes have diameters <2.3 μm. P. autumnale morphotypes were only common in mats at <12 m depth. Mats containing abundant P. autumnale morphotypes were smooth, whereas mats with few P. autumnale morphotypes contained small peaks and protruding bundles of filaments, suggesting that the absence of P. autumnale morphotypes allowed small‐scale topography to develop on mats. Comparisons of living filaments and mold diameters suggest that P. autumnale morphotypes were present early in stromatolite growth, but disappeared from the community through time. We hypothesize that the mat‐smoothing behavior of P. autumnale morphotypes inhibited nucleation of stromatolite branches. When P. autumnale morphotypes were excluded from the community, potentially reflecting a rise in lake level, short‐wavelength roughness provided nuclei for stromatolite branches. This growth history provides a conceptual model for initiation of branched stromatolite growth resulting from a change in microbial community composition.